Optimalisasi Wakaf Uang sebagai Instrumen Pemberdayaan Ekonomi Umat di Indonesia - Ilpan Ilpan (JEBI (Jurnal Ekonomi dan Bisnis Islam), 2026)
Cash waqf is one of the instruments of Islamic social finance that has significant potential to support economic development and improve community welfare. Unlike traditional waqf, which is generally in the form of land or buildings, cash waqf offers greater flexibility in its management and utilization. This article aims to examine the role of cash waqf as a source of community economic empowerment in Indonesia, as well as to identify the opportunities and challenges in its development. The method employed in this study is a literature review through the examination of various references, scientific journals, and regulations related to cash waqf. The findings indicate that cash waqf has considerable potential to support financing in the fields of education, healthcare, micro-enterprises, and other social programs. However, its implementation still faces several challenges, including low public literacy, limitations in management practices, and the suboptimal utilization of digital technology. Therefore, collaboration among the government, waqf institutions, and society is necessary to enhance the role of cash waqf in national economic development.